- Effect of Puerarin administration on Serum serum NOD-like receptor protein 3 (NLRP3) inflammasome, C1q/TNF-Related Protein 3 (CTRP3) and lipoprotein-associated phospholipase 2 (Lp-PLA2) levels.: Serum NOD-like Receptor Protein 3 Inflammasome, C1q/TNF-related Protein 3 and Lipoprotein-associated Phospholipase 2 Levels - wang, dan (Journal of Medical Biochemistry, 2025)
Introduction: Coronary heart disease (CHD) is a cardiovascular disease with a high incidence in elderly patients. This article aimed to evaluate the clinical efficacy of puerarin (Pue) as an adjuvant therapy in elderly patients with CHD, and the effects of Pue on serum NOD-like receptor protein 3 (NLRP3) inflammasome, C1q/TNF-Related Protein 3 (CTRP3) and lipoprotein-associated phospholipase 2 (Lp-PLA2) levels. Method: A total of 118 elderly patients with CHD admitted to Beijing University of Chinese Medicine Third Affiliated HospitaL and 24 induced CHD rat models were enrolled. The controls received conventional treatment, and the study subjects received 5% glucose injection 500mL+Pue injection 0.4g, intravenous drip once a day, 7 days as a course of treatment based on conventional treatment. The improvement of clinical symptoms in patients with CHD and the changes of serum NLRP3 inflammasome, CTRP3 and Lp-PLA2 levels in patients and experimental rats were compared. Result: Relative to the controls, the study subjects had a reduction in the number of angina episodes and an increase in exercise tolerance. In addition, the serum NLRP3 inflammasome and Lp-PLA2 were distinctly decreased, and the serum CTRP3 was distinctly raised in study subjects and experimental rats. C onclusion: Pue may improve the inflammatory state and lipid metabolism in patients with CHD by inhibiting NLRP3 inflammasome and regulating the levels of biomarkers such as CTRP3 and Lp-PLA2, thereby reducing symptoms and improving the quality of life.